Manfaat Seni Rupa dalam Merangsang Kreativitas Anak Usia Dini - Kiraniawati Telaumbanua; Berkati Bu’ulolo (Institut Nalanda, 2024)
Art learning is a child's education that focuses on the development of visual intelligence, also known as visual intelligence. In this context, children are encouraged to have the ability to understand objects thoroughly and in detail. The purpose of this research is to provide an understanding to teachers that the benefits of fine arts are very beneficial for early childhood, this research method uses descriptive qualitative research methods with data review from case studies, literature studies, and books as reference references. The results of this study are in the benefits of fine arts for early childhood can develop children's Fine Motor Skills, develop Imagination and Creativity through fine arts, Increase Problem Solving Skills and Increase Emotional Intelligence.